Pendidikan Islam Multikultural di Era Global: Kajian Pustaka tentang Tantangan dan Implikasi - David Ricardo; Amri Saputra; Mahmud Arif (Journal of Educational Research and Learning Analytics, 2025)
This study aims to analyze current issues in multicultural Islamic education and examine its implications and developmental direction in the global era. Multicultural Islamic education is understood as a paradigm that emphasizes the universal Islamic values of justice, tolerance, and brotherhood as the foundation for living together within diversity. This research employs a literature review method by examining scientific works published between 2015 and 2025 through a descriptive-analytical approach to identify foundational concepts, contemporary issues, implementation challenges, and both theoretical and practical implications. The findings show that multicultural Islamic education still faces problems such as intolerance, radicalism, curriculum homogenization, and weak teacher competence in inclusive pedagogy. These challenges are intensified by globalization and the digitalization of values, which influence the mindset of younger generations. Therefore, Islamic education needs to be developed in a humanistic, contextual, and adaptive manner through integrative curriculum reform, character strengthening based on universal Islamic values, and interdisciplinary collaboration to build more inclusive and civilized learning.